2011
DOI: 10.1111/j.1365-2850.2011.01704.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychodrama: an innovative way of improving self-awareness of nurses

Abstract: The aim of this educational session was to form a group interaction model for improving the self-awareness of nurses via psychodrama. The structured group interaction session was conducted three times, with three separate groups, during the 'Intensive Care Nursing' training programme at a teaching hospital in Ankara. An assessment was made using the written records and observations of the group director and co-directors and feedback from nurses regarding the session. The nurses were highly motivated, adapting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…3,4) Psychodrama/action methods enhanced understanding of others and self-related concepts. 11,29) Comparing contextbased learning methods, collaborating training, and traditional training, it was concluded that the context-based learning method and collaborating training increased respect, self-related concept, communication skills, and responsibilities in comparison to the traditional method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4) Psychodrama/action methods enhanced understanding of others and self-related concepts. 11,29) Comparing contextbased learning methods, collaborating training, and traditional training, it was concluded that the context-based learning method and collaborating training increased respect, self-related concept, communication skills, and responsibilities in comparison to the traditional method.…”
Section: Discussionmentioning
confidence: 99%
“…By using the action method, one could learn about oneself more deeply, 11) see and experience role models, 12) and have the opportunity to discover different viewpoints. 29) Among the studies reviewed, not all approaches mainly focused on increasing self-awareness. For example, the study using the context based learning method, collaborating training, and traditional training 6) compared learning, attitude, behavior, and self-awareness levels among these three different types of approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychodrama techniques to re‐enact the helper–helped dynamic in developing and improving self‐awareness have been suggested (Oflaz et al . ). It is worth noting that given the significance of stigma reported in this study, consideration would need to be given to how perceived and actual stigma may act as a barrier for the adopted strategies.…”
Section: Discussionmentioning
confidence: 97%
“…It is developed in an atmosphere of play and freedom, to achieve expressiveness when articulated in the dramatic or theatrical background, with originality and creativity 14 . Psychodrama provides opportunities for reflective practice and meaningful learning [15][16][17] and can be used for teaching various communication skills, including listening skills, asking questions, counseling, care, and communication in sensitive situations [18][19][20] . The process of dramatization can also provide an increase in learning of abstract concepts because role playing provides the experience of aspects that cannot be easily expressed in words 21 .…”
Section: Introductionmentioning
confidence: 99%